Liver transplantation for HCC within and beyond Milan Criteria: single center experience with literature review - Tırnova, İ.; Kanmaz, T. (Frontiers in Surgery, 2025)
IntroductionThe Milan Criteria (MC) are widely accepted as the standard patient selection criteria for liver transplantation (LT). However, patients who exceed these criteria may still benefit from transplantation. Various extended criteria have been published. This study aimed to evaluate survival outcomes in hepatocellular carcinoma (HCC) patients undergoing LT, comparing those within and beyond MC, and to review the role of extended criteria in LT.MethodsThis retrospective, single-center study included adult patients who underwent LT at Koç University between 2018 and 2024. Pathological data were used to categorize patients into two groups: those within MC and beyond MC. Preoperative data and postoperative overall and disease-free survival rates were compared between these groups. Additionally, a comprehensive literature review of studies evaluating extended criteria for LT in HCC patients was conducted.ResultsA total of 45 adult patients were included in the analysis. There were 23(51.1%) patients within MC, and 22(48.9%) patients in the beyond MC group. Demographics, donor types, graft types, tumor differentiations, Child scores, MELD scores, ischemia times, length of intensive care unit stays, length of hospital stays, and mortality rates were similar (p > 0.05). Tumor count, total tumor diameter, and microvascular invasion rates were statistically higher in patients beyond MC (p < 0.05). Survival analyses revealed no statistically significant differences in 1-year, 3-year, and 5-year survival rates of the patients (p > 0.05).ConclusionThis study highlights the potential for liver transplantation in HCC patients exceeding the Milan Criteria, with survival outcomes comparable to those within the Milan Criteria in certain cases. Despite numerous studies in the literature, optimal criteria for LT patient selection in beyond MC HCC have not been established. An optimal guideline that will help to better understand tumor behavior, guide the decision-making and timing of liver transplantation (LT), and ultimately improve post-transplant outcomes remains a key objective for future research.